(untitled) (Research, Society and Development, 2022)
Objective: describe bibliometric indicators of national and international scientific production on bathing term newborns and its historical evolution in the last six decades. Method: bibliometric study, using Lotka, Bradford and Zipf laws. The literature survey was carried out in December 2020 and studies that addressed the topic of bathing in term newborns published between 1970 and 2020 were included. Results: the sample consisted of 83 publications with a predominance of studies carried out in North America in the English language and the most frequent types of studies were randomized controlled ones. The articles were written by 367 different authors, identified in 44 journals. Main keywords found: newborn, bathing and skin care. Conclusion: this research made it possible to describe the changes and gaps in this scenario in the national and international contexts and to encourage productions with a high level of evidence.